Meta-analysis of the effect of applying scientifically oriented learning models on physics learning outcomes - Hepi, Nur; Desnita, Desnita; Putra, Amali; Emilianur, Emilianur (Universitas Muhammadiyah Mataram, 2024)
The aim of this research is to review the influence of implementing scientifically oriented learning models on students' physics learning outcomes. This research method summaries relevant research published in 2013-2023. The subject of this research is 71 relevant articles that have been published in SINTA and international accredited journals. The results show that: 1) based on the four models analyzed; there are project-based learning (PjBL), inquiry and discovery model, which has ES in high category. The problem-based learning PBL model has an ES in the medium category. 2) Based on physics material units, show that there are two PBL models, namely thermodynamic material units and others that have an ES in the high category. There are two PjBL models, namely thermodynamic material units and waves, which have an ES in very high category. There are three inquiry models; mechanics, thermodynamics, and other material units with ES in the high and very high categories. There are four discovery models ; mechanics, thermodynamics, electricity, magnetism, and optical waves, which have ES in the high and very high categories. 3) Based on high school class level analysis, show that there is one PBL model, namely class X which has ES in the high category. There are two PjBL models; class X and XII which has ES in very high, and high categories. There are two inquiry models, namely classes X and XI which have ES in the high category. There is one discovery model, class X which has ES in the high category.